Planetary roulette : gambling with the climate. - REPETTO, Robert (1997)
Discusses how the greatest obstacle to confronting the biggest environmental problem in history may not be scientific so much as political : the lack of international mechanisms that would enable 167 nations to bridge their differences and craft policies as effective as they are equitable.